2016
DOI: 10.1016/j.vetpar.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Severe seizures in pigs naturally infected with Taenia solium in Tanzania

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…These were naturally infected with T. solium , and diagnosis was based on tongue inspection. The infected pigs were part of an experimental behavioral study conducted over 14 consecutive days and in which seizures were observed in two out of 16 pigs ( Trevisan et al, 2016 ). Two infected pigs with seizures and T. solium cysts, four infected pigs without seizures but with cysts and one non-infected control pig originating from a commercial Danish pig farm, were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were naturally infected with T. solium , and diagnosis was based on tongue inspection. The infected pigs were part of an experimental behavioral study conducted over 14 consecutive days and in which seizures were observed in two out of 16 pigs ( Trevisan et al, 2016 ). Two infected pigs with seizures and T. solium cysts, four infected pigs without seizures but with cysts and one non-infected control pig originating from a commercial Danish pig farm, were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…However, a significant proportion of individuals with neurocysticercosis remain asymptomatic ( de Almeida and Torres, 2011 ), which may partly be ascribed to the fact that it can take years from infection time until signs start showing ( Garcia et al, 2003 ). Recently, Trevisan et al (2016) reported for the first time seizures in pigs with T. solium neurocysticercosis ( Trevisan et al, 2016 ). Previous to this, clinical signs in pigs have not been studied thoroughly, and pigs have to a large extent been considered not to be clinically affected by the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations of NCC differ, varying from asymptomatic to severe (Winkler, 2013;Trevisan et al, 2016). Seizures are the most common presentation of NCC in humans (Carpio and Romo, 2014) occurring in about 60-90% of symptomatic infections (Rodrigues et al, 2012;Carpio et al, 2013), although incidence varies in different regions according to socioeconomic and cultural practices (Del Brutto, 2013b;Winkler, 2013).…”
Section: Disease In Humansmentioning
confidence: 99%
“…Recent findings reported that seizures also occur in pigs with NCC and disease negatively affects their behaviour, posing a further burden on the welfare of affected animals [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%